ANALISIS TITIK PULANG POKOK (TPP) USAHA PEMBIBITAN CENGKEH DI DESA PULIAS KECAMATAN OGODEIDE KABUPATEN TOLITOLI (STUDI KASUS CV.NURHAFIZA) - Yanti Sasmita; Salawati; Tamrin (FAKULTAS PERTANIAN UNIVERSITAS ALKHAIRAAT, 2020)
This study aims to determine the amount of production and business acceptance of clove nurseries CV. Nurhafiza in Pulias village ogodeide district tolitoli regency. The time of the study was conducted in November to December 2018. The determination of the data collection method was derived from primary data and secondary data and the analysis used was the break even point (BEP). The result showed that the principal return point value was reached during the production of 3,922 trees . this means that the production of 3,922 clove nursery business CV. Nurhafiza in pulias village, Ogodeide Tolitoli Regency, was not profitable and did not lose or TR=TC. Break even point revenue is Rp. 15.689.990, which means that at Rp. 15. 689.990, CV. Nurhafiza in Pulias Village , Ogodeide Tolitoli Regency, was not profitable and did not lose or TR=TC.